Germination Capacity of Helianthus annuus Less Seeds on Soil Media Contaminated by Waste - Wahyu Lestari; Sujarwati; Atria Martina; Imelda Wardani; Daryono (Jurnal Biologi Tropis, 2023)
Used oil waste is often dumped on the ground around the workshop, causing soil pollution which can reduce the function of the soil. The most difficult contaminants in used oil waste to decompose are hydrocarbon compounds, which are highly toxic, polycyclic aromatic hydrocarbons (PAHs). The concentration of oil hydrocarbon contaminants in a sample is determined by measuring the total petroleum hydrocarbon (TPH) concentration. This study was conducted to determine the germination ability of Helianthus anuus, Less seeds on soil media contaminated with waste oil at different concentrations of Total Petroleum Hydrocarbon (TPH). The results showed that the concentration of TPH in the media could inhibit the speed of seed germination. Treatment with low concentration of TPH 2.7% in the media increased % germination, shoot and root length and sprout biomass compared to the medium/intermediate (8.00%) and high (12.26%) TPH treatments and controls. However, there was no significant difference between all treatments regarding germination time and shoot length, although in the low TPH treatment (2.70%) there was a tendency for germination time to be faster than the other treatments, as well as to shoot length which was longer than the other treatments. The higher TPH concentration in the media can inhibit germination time, germination percentage, shoot and root length and biomass. Morphological observations of the growth of sprouts showed an inhibition of root hair formation along with the high TPH content in the media, but all treatments did not affect the growth of the shoots.